2021
DOI: 10.1109/access.2021.3095420
|View full text |Cite
|
Sign up to set email alerts
|

Load Forecasting Under Concept Drift: Online Ensemble Learning With Recurrent Neural Network and ARIMA

Abstract: Rapid expansion of smart metering technologies has enabled large-scale collection of electricity consumption data and created the foundation for sensor-based load forecasting on individual buildings or even the household level. With continuously growing energy consumption, the importance of energy management including load forecasting is increasing in order to remedy the energy effect on the environment. Numerous machine learning techniques have been proposed for sensor-based load forecasting but most are offl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Nowadays, linear regression is often used as a comparative method to evaluate the performance of more elaborated machine learning methods. Studies that used ARIMA as an energy prediction method for buildings may be found in [38][39][40].…”
Section: Figurementioning
confidence: 99%
“…Nowadays, linear regression is often used as a comparative method to evaluate the performance of more elaborated machine learning methods. Studies that used ARIMA as an energy prediction method for buildings may be found in [38][39][40].…”
Section: Figurementioning
confidence: 99%
“…A similar phenomenon occurs in dynamic electrical environments, which involves S.G. and D.G.M. Some other studies considering the concept drifts are: Jagait, R. K., et al [40] presented an ensemble approach for online learning using R.N.N.s and ARIMA. The study proposed an adaptive model based on concept drift using R.N.N.s and considered ARIMA for creating a rolling window operation to create an online scenario for the ensemble model.…”
Section: Adaptive Models With Concept Driftmentioning
confidence: 85%
“…These models are capable of self-learning and adaptation to changes. Though the researchers are covering some dynamics in other fields for the transformation of models in classification applications [49][50][51], some propositions in regression works also exist [25,40]. Still, in regression, many features need to be incorporated when the task is specifically of electrical load forecasting to enable the model to be eligible for multi-modality or Smart Grid.…”
Section: Tentative Proposed Frameworkmentioning
confidence: 99%
“…First, the proposed methodology is guided by the ensemble methods (learning) concept, where an improved predictive performance is expected when employing/combining multiple methods versus any of the individual methods. More specifically, this work is centered on a stacking ensemble type approach, which in a broad sense involves training a machine learning method to merge the predictions of some other methods [41]. To reinforce this point, the literature in the forecasting field documents report that when dealing with an unstable and varying data pattern, it is convenient to use dissimilar models to improve time-series forecasting accuracy [42].…”
Section: Proposed Methodologymentioning
confidence: 99%